Latin American urban development into the 21st century: Towards a renewed perspective on the city - Dennis Rodgers; Jo Beall; Ravi Kanbur (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper argues for a more systemic engagement with Latin American cities, contending it is necessary to reconsider their unity in order to nuance the 'fractured cities' perspective that has widely come to epitomise the contemporary urban moment in the region. It begins by offering an overview of regional urban development trends, before exploring how the underlying imaginary of the city has critically shifted over the past half century. Focusing in particular on the way that slums and shantytowns have been conceived, it traces how the predominant conception of the Latin American city moved from a notion of unity to a perception of fragmentation, highlighting how this had critically negative ramifications for urban development agendas, and concludes with a call for a renewed vision of Latin American urban life.
Keywords: O18; O54; N96; Z19; 330; Latin America; urbanization; cities; slums; urban development; Stadtentwicklung; Urbanisierung; Lateinamerika